Mathematical Model For Determination the Increase in Operational Cost of Transmission Line From HAD3 to QIM3 in Electric Power System - Tawfiq, Luma; Ismail, Manar (Iraqi Journal of Science, 2024)
The transformation of a physical system to mathematical base is very important due to analysis of the systems behavior. In this paper an electric power system is considered, we design mathematical model for the determination of the increase in operational cost of transmission line from Haditha Dam substation to Qa'im substation . We derived relations which the approximate distance for VARS transmission must satisfy with considering minimum losses in the system. MATLAB computer programming is used to obtain the numerical results. The developed mathematical model and the numerical results could be useful to electric power systems engineers